The Impact Of Delaying Elective Surgeries On Patient Safety During Covid-19: Literature Review - Ulya Serly Amrillah (CV. AFDIFAL MAJU BERKAH, 2026)
The COVID-19 pandemic has had a major impact on the global healthcare system, including the postponement of elective operations due to limited resources and efforts to prevent the transmission of the virus. Globally, more than 28 million operations were postponed, including in Indonesia. Delays have an effect on patient safety because they risk having a serious impact on patients. This study aims to understand the impact of delaying elective surgeries on patient safety during the COVID-19 pandemic. The design of this research is a literature review. Searching for articles through the Pubmed, Science Direct, and Google Scholar databases (2020-2025) using the keywords